Molecular and epidemiologic investigation of a rhinovirus outbreak in a neonatal intensive care unit. (5th December 2018) - El Idrissi, Kenza Rahmouni; Isabel, Sandra; Carbonneau, Julie; Lafond, Martine; Quach, Caroline; Caya, Chelsea; Fontela, Patricia S.; Beltempo, Marc; Boivin, Guy; Lefebvre, Marie-Astrid; Papenburg, Jesse
Abstract : We performed a molecular and epidemiologic study of a healthcare-associated rhinovirus outbreak to better understand transmission in neonatal intensive care settings. Sequencing of the 7 outbreak strains revealed 4 distinct clades, indicating multiple sources. A single clade infected 3 patients in adjacent rooms, suggesting horizontal transmission. We observed 1 rhinovirus-associated death.